The Mdm2 RING domain C-terminus is required for supramolecular assembly and ubiquitin ligase activity - Poyurovsky, Masha V (Nature Publishing Group, 2007)
Mdm2, a key negative regulator of the p53 tumor suppressor, is a RING-type E3 ubiquitin ligase. The Mdm2 RING domain can be biochemically fractionated into two discrete species, one of which exists as higher order oligomers that are visible by electron microscopy, whereas the other is a monomer. Both fractions are ATP binding and E3 ligase activity competent, although the oligomeric fraction exhibits lower dependence on the E2 component of ubiquitin polymerization reactions. The extreme C-terminal five amino acids of Mdm2 are essential for E3 ligase activity in vivo and in vitro, as well as for oligomeric assembly of the protein. A single residue (phenylalanine 490) in that sequence is critical for both properties. Interestingly, the C-terminus of the Mdm2 homologue, MdmX (itself inert as an E3 ligase), can fully substitute for the equivalent segment of Mdm2 and restore its E3 activity. We further show that the Mdm2 C-terminus is involved in intramolecular interactions and can set up a platform for direct protein–protein interactions with the E2.